Irrelevance of competitive advantage for the benefits of international trade - Eckhard Siggel (The Open Economics Journal, 2012)
International competitiveness is often regarded as crucial for the attainment of gains from trade, which may lead policy makers to subsidize exports. This view is based on confusion between the concepts of competitive and comparative advantage. The paper argues that when comparative advantage is defined and measured appropriately, not limiting it to the Ricardian and Heckscher-Ohlin models, it becomes a necessary condition for the attainment of gains from trade and it applies to all forms of trade that lead to economy-wide gains. The paper proceeds by reviewing first the concepts and measurements of comparative and competitive advantage. It shows that in order to result in economy-wide benefits, known as gains from trade, trade needs to be based on comparative advantage. It also points to implications for the design of trade and industrial policies.
Keywords: F10; F12; 330; comparative advantage; competitive advantage; international competitiveness; gains from trade; intra-industry trade